Recruitment of Oct4 protein to UV-damaged chromatin in embryonic stem cells - Bártová, Eva; Šustáčková, Gabriela; Stixová, Lenka; Kozubek, Stanislav; Legartová, Soňa; Foltánková, Veronika (PloS one, 2011)
BACKGROUND: Oct4 is a specific marker of embryonic stem cell (ESC) pluripotency. However, little is known regarding how Oct4 responds to DNA damage. Here, we investigated whether Oct4 recognizes damaged chromatin in mouse ESCs stably expressing GFP-Oct4. These experiments should contribute to the knowledge of how ESC genomic integrity is maintained, which is crucial for potential application of human ESCs in regenerative medicine. METHODOLOGY/PRINCIPAL FINDINGS: We used time-lapse confocal microscopy, microirradiation by UV laser (355 nm), induction of DNA lesions by specific agents, and GFP technology to study the Oct4 response to DNA damage. We found that Oct4 accumulates in UV-damaged regions immediately after irradiation in an adenosine triphosphate-dependent manner. Intriguingly, this event was not accompanied by pronounced Nanog and c-MYC recruitment to the UV-damaged sites. The accumulation of Oct4 to UV-damaged chromatin occurred simultaneously with H3K9 deacetylation and H2AX phosphorylation (γH2AX). Moreover, we observed an ESC-specific nuclear distribution of γH2AX after interference to cellular processes, including histone acetylation, transcription, and cell metabolism. Inhibition of histone deacetylases mostly prevented pronounced Oct4 accumulation at UV-irradiated chromatin. CONCLUSIONS/SIGNIFICANCE: Our studies demonstrate pluripotency-specific events that accompany DNA damage responses. Here, we discuss how ESCs might respond to DNA damage caused by genotoxic injury that might lead to unwanted genomic instability.
Keywords: histony; Gene Expression Regulation; Chromosomal Proteins, Non-Histone; poškození DNA; adenosintrifosfát; 53BP1; fibroblasty; Cell Nucleus; DNA Damage; Fibroblasts; fosforylace; Transcription, Genetic; oktamerní transkripční faktor 3; Phosphorylation; Tumor Suppressor p53-Binding Protein 1; buněčné jádro; DNA vazebné proteiny; chromatin; ultrafialové záření; embryonální kmenové buňky; genetická transkripce; Chromatin; Embryonic Stem Cells; kinetika; Animals; zvířata; regulace genové exprese; Ultraviolet Rays; myši; regenerativní lékařství; Regenerative Medicine; chromozomální proteiny, nehistonové; Adenosine Triphosphate; Histones; Octamer Transcription Factor-3; Mice; DNA-Binding Proteins; Kinetics